Application of Microbial Induced Calcite Precipitation (MICP) Technology in Geotechnical and Geo-Environmental Engineering: A Review - Muhammad, I. S.; Kurna , B. B.; Ibn Abubakar, B. S. U. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
One of the most recent areas of research in geotechnical and geo-environmental engineering is bio-mineralization, a natural process in living organisms, also known as Microbial Induced Calcite Precipitation. It is the formation of calcium carbonate from a supersaturated solution due to the presence of microbial cells and bio-chemical activities. In the process, microbes secrete metabolic products that reacts with ion in the medium to precipitate minerals. Through this process, soil improvement/remediation have been investigated and proven reliable with minute carbon print as compared to conventional binders. This paper presents an overview on the wide application of Microbial Induced Calcite Precipitation in the areas of geotechnical and geo-environmental engineering with the mechanisms and factors influencing its performance explained. The work has also considered both laboratory and field scale researches conducted in these areas. The key contribution of this work is the compilation of different approaches in soil stabilization and remediation, via urease producing microbes, in single source. It also outlined different treatment dosages based on environmental conditions suitable to soil types.